Same, same but different: the Nordic EU members during the crisis - Bäckman, Pernilla; Hassing Nielsen, Julie; Jokela, Juha; Lewander, Jakob; von Sydow, Göran (Stockholm, 2015)
"The euro crisis has left no EU member state unaffected. European cooperation and solidarity has for many years been put to the test in a way which has no parallel in the post-war period. Financial turmoil has generated economic straits and political shifts in various countries. The responses to these challenges have differed between countries, as well as the political consequences.